International Students’ Social Experiences of Studying a Postgraduate Course in Britain: A Case Study of Cardiff University - Nghitoolwa, Hilya (Papanda Publisher, 2025)
The study explores international master's students' social experiences at Cardiff University and the support provided during the 2020 academic year, when COVID-19 was at its peak. This research draws upon rich qualitative data from 20 purposively selected participants. The selection criteria ensured gender balance, international representation, diverse undergraduate backgrounds, and inclusion of both remote and UK-based postgraduate students from various academic programs. Data were collected utilising semi-structured one-to-one Zoom interviews. The study used NVivo 12 Pro to conduct thematic data analysis. The study found that international postgraduate students at Cardiff University generally had positive social experiences, forming friendships and joining student societies. However, COVID-19 restrictions limited in-person interactions. The university provided support services, including English language help, counselling, well-being services, and international student support, such as scholarships. The findings of this research recommended that the university communicate frequently with international students about all the activities and student societies on campus. Likewise, the university should hold online events for students to meet other foreign students virtually. Universities must acknowledge that encouraging international postgraduate students to have a pleasant social experience is essential to advancing diversity, inclusivity, and cross-cultural interaction as well as academic achievement on campus. Similarly, COVID-19 constraints highlight the necessity for colleges to create adaptable and creative strategies for social interaction, such as growing online communities and virtual gatherings.